2014
DOI: 10.1002/dvg.22756
|View full text |Cite
|
Sign up to set email alerts
|

Branching out: Origins of the sea urchin larval skeleton in development and evolution

Abstract: It is a challenge to understand how the information encoded in DNA is used to build a three dimensional structure. To explore how this works the assembly of a relatively simple skeleton has been examined at multiple control levels. The skeleton of the sea urchin embryo consists of a number of calcite rods produced by 64 skeletogenic cells. The ectoderm supplies spatial cues for patterning, essentially telling the skeletogenic cells where to position themselves and providing the factors for skeletal growth. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 93 publications
(160 reference statements)
0
44
0
Order By: Relevance
“…3). This is an important conclusion, which argues against a model in which VEGF signaling is the only or the principle mediator of skeletal patterning in sea urchin embryos, as has been previously suggested (Duloquin et al, 2007;Lyons et al, 2011;Adomako-Ankomah and Ettensohn, 2013;McIntyre et al, 2014). Late VEGFR inhibition (via axitinib) blocks secondary skeletogenesis, which has been interpreted as reflecting a block to biomineralization (Adomako-Ankomah and Ettensohn, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…3). This is an important conclusion, which argues against a model in which VEGF signaling is the only or the principle mediator of skeletal patterning in sea urchin embryos, as has been previously suggested (Duloquin et al, 2007;Lyons et al, 2011;Adomako-Ankomah and Ettensohn, 2013;McIntyre et al, 2014). Late VEGFR inhibition (via axitinib) blocks secondary skeletogenesis, which has been interpreted as reflecting a block to biomineralization (Adomako-Ankomah and Ettensohn, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…Armstrong, Hardin and McClay later used microsurgical transplants to demonstrated that the nickel-mediated patterning defect was specific to the ectoderm and not the PMCs (Armstrong et al, 1993). Subsequent experiments have confirmed and corroborated these results (reviewed by Adomako-Ankomah and Ettensohn, 2014;McIntyre et al, 2014). Throughout their migration, the PMCs extend thin filopodia that contact the ectoderm (Gustafson and Wolpert, 1999;Miller et al, 1995).…”
Section: Introductionmentioning
confidence: 80%
“…Most of the proteins in these clusters were linked to eukaryotic translation initiation factor 3 subunit D (Eif3d), neuron navigator Nav1/2/3, kinesin protein KifC3L2, calcium‐activated potassium channel Kncma1, axonemal dynein Axndhc3h, Cadherin4L, several zinc finger proteins (e.g., Z156, Z35), growth factor receptor (Grb2), and transcription factors (e.g., TFIIB/GTF2b, TfIID, SOX, KEN2, GTF3C5, AP‐1, ELT‐2, KAY; Table S13). The presence of several ophiuroid orthologs of sea urchin embryonic development (Vaughn et al., 2012) and the remarkable resemblance in the expression of regulatory genes between both groups (McIntyre, Lyons, Martik, & McClay, 2014) suggest a similar molecular makeup of their major embryonic territories (i.e., skeletogenic, endomesoderm, and ectoderm; Dylus et al., 2016). Within echinoids, 11,814 orthologous clusters were identified as unique for sea urchins, from which 4,167 were shared among M. franciscanus , S. purpuratus, and L. variegatus (Figure 2c).…”
Section: Resultsmentioning
confidence: 99%